Synthesis, Spectroscopic and Computational Studies of Some Metals Chelates with Chromene-2-one and Pyrazine-Based Ligands - Taghreed Mohy Al-Deen Musa; Mahmoud Najim Abid Aljibouri; Bayader Fadhil Abbas; Nahid Hasani (Indonesian Journal of Chemistry, 2020)
The present paper deals with the synthesis of cobalt(II), nickel(II), copper(II) and cadmium(II) complexes with two bidentate ligands, L1 (3-(quinoxaline-2-yl)-coumarin) and L2 (2-methylene-2H-chromene-3-(methyl carbonimidic)thioanhydride). The L1 ligand was prepared by treating w-bromo-3-acetylcoumarin with 1,2-phenylenediamine whereas the ligand L2 was prepared through substitution reaction ofw-bromo-3-acetylcoumarin with potassium thiocyanate in ethanol medium. The confirmation of the structures for L1 and L2 were done by (C.H.N.S.) elemental analysis, FT-IR, NMR and mass spectra. The metal complexes of cobalt(II), nickel(II), copper(II) and cadmium(II), with L1 and L2, were prepared and isolated in the solid state then characterized by (C.H.N.M) elemental analysis, proton and carbon-13 NMR, FT-IR and mass spectra. Furthermore, the thermal analysis (TG-DSC) for some complexes assisted us in the elucidation of the suggested structures of complexes and confirmed their thermal stability. The results obtained from elemental analysis, magnetic susceptibility and thermal analysis confirmed that all metal complexes were formed in 2:1 molar ratio of ligand to metal with octahedral structures except cadmium(II) complexes which were in a tetrahedron geometry with 1:1 mole ratio. The complexes are found to be soluble in DMF and DMSO. The results obtained from TG-DSC analysis revealed that the metal complexes were thermally stable with point decomposition over 350 °C. The DFT/TDDFT calculations were carried out to provide the electronic structures and spectra of the compounds.